2003
DOI: 10.1016/s0885-3924(03)00321-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Modified Rotterdam Symptom Checklist for use with cancer patients in the United States

Abstract: The Rotterdam Symptom Checklist (RSCL) is a well-known instrument for the assessment of symptom-related distress among cancer patients. Despite its broad application, the utility of the RSCL with patients of some cancers is hindered by the omission of several important physical symptoms and methodological limitations of previous validation studies. The aims of the present study were to modify the RSCL through the addition of several physical symptoms and to subsequently validate the modified version of the Rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 38 publications
2
39
0
4
Order By: Relevance
“…Life quality is consisted of a great many sub dimensions such as physical, psychological, social and spiritual, and the density of symptoms experienced by children threatens these areas (Stein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life quality is consisted of a great many sub dimensions such as physical, psychological, social and spiritual, and the density of symptoms experienced by children threatens these areas (Stein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the disorders related to such symptoms create a negative effect on the life quality of cancer patients and may reduce the compliance to the treatment suggestions (Stein et al, 2003). Frequent hospitalization, problems related to cancer treatment, pains that are not stopped, loss of self-control, inability to do basic activities, being hospitalized and not being able to meet the playing need because of various treatments, being separated from friends and school negatively affects the child's life quality.…”
Section: Introductionmentioning
confidence: 99%
“…Women with breast cancer suffer physical symptoms such as changes in taste, alopecia, nausea, vomiting, mucositis and fatigue due to chemotherapy (Stein et al, 2003). These side effects can lead to psychological problems which affect the patient's activities of daily living (Erci and Karabulut, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Rotterdam Symptom Checklist (RSCL) [24] was used to measure both the prevalence and distress level associated with specific symptoms that may occur in cancer patients. The original 34-item checklist was modified by adding an additional nine symptoms relevant to the purposes of the primary study; however, these additional symptoms did not influence the nutrition impact symptoms of interest to this secondary analysis.…”
Section: Data Collectionmentioning
confidence: 99%